Factors that determining the selection of takaful agent amongst staffs of schools at Sura, Dungun / Mohd Hafiz Abdullah @ Ismail - Abdullah @ Ismail, Mohd Hafiz (2009)
In Malaysia, the takaful industry had grown rapidly inspired by the existing needs of the Muslim society to the Syariah-compliant alternative to conventional. The needs and demand by the Muslims customers as well as the non-Muslims customers caused to the used of agency. In takaful, the principle of al-wakalah is underlying to represent an insurance company. Bank Negara Malaysia was reported in 2004 that the number of agent in takaful industry is huge and going to be growth rapidly. By the rapid growth of takaful agents in the takaful industry had change the way of the customers in getting the takaful in which the customers prefer to apply insurance direct through Agency Company and agents. In general, the objective of this research is to identify the factors that determine the selection of takaful agent and also want to identify the difference that may occur between demographic factors and the selection on takaful agent. The researcher conducts this study among staffs of schools at Sura, Dungun, Terengganu that involved 73 respondents. The research sampling was undertaken using convenient sampling which is easily to researcher to take large number of respondents. This research was analyzed by using statistic descriptive analysis (frequency distribution), reliability analysis, correlation coefficient, regression, T-test and analysis of variance (ANOVA). All the three factors in this study are service quality, promotion and perception that need to be alert by the takaful agent in order their product to be choose.